1997
DOI: 10.1006/viro.1997.8823
|View full text |Cite
|
Sign up to set email alerts
|

Basic Amino Acid Residues at the Carboxy-Terminal Eleven Amino Acid Region of the Phosphoprotein (P) Are Required for Transcription but Not for Replication of Vesicular Stomatitis Virus Genome RNA

Abstract: The phosphoprotein (P) of vesicular stomatitis virus (VSV) serotypes New Jersey [P(NJ)] and Indiana [P(I)] contains a highly conserved carboxy-terminal domain which is required for binding to the cognate N-RNA template as well as to form a soluble complex with the nucleocapsid protein N in vivo. We have shown that the deletion of 11 amino acids from the C terminal end of the P(I) protein abolishes both the template binding and the complex forming activity with the N protein. Within this region, there are conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 55 publications
1
40
0
Order By: Relevance
“…Most recently, Gupta et al (23) observed that a transcriptionally inactive P mutant can still form a tripartite complex with the N and L proteins and can function as a replicase for the synthesis of full-length genomic RNA. This study, along with other studies (8,26,44), suggests that the transcriptase and replicase complexes of VSV are two distinct entities. Phosphorylation of the P protein may also play a role in the virus life cycle, during which an infectious unit is assembled in an orchestrated manner involving the transcription, replication, and assembly of functional nucleocapsid templates.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Most recently, Gupta et al (23) observed that a transcriptionally inactive P mutant can still form a tripartite complex with the N and L proteins and can function as a replicase for the synthesis of full-length genomic RNA. This study, along with other studies (8,26,44), suggests that the transcriptase and replicase complexes of VSV are two distinct entities. Phosphorylation of the P protein may also play a role in the virus life cycle, during which an infectious unit is assembled in an orchestrated manner involving the transcription, replication, and assembly of functional nucleocapsid templates.…”
supporting
confidence: 82%
“…The P protein of VSV has a modular structure. In vitro studies as well as studies with transfected cells using DI RNAs or minigenomic RNAs strongly suggest that the phosphorylation of different structural domains of the P protein regulates its multiple functions in viral genome transcription and replication (2,3,7,8,16,17,26,44,53). In the present study, we addressed the role of P protein phosphorylation in the life cycle of VSV.…”
Section: Vol 78 2004 P Phosphorylation Is Essential For Vsv Growth mentioning
confidence: 99%
“…The phosphorylation of P in nonsegmented negative-stranded RNA virus is thought to play a critical role in virus RNA synthesis (19). Mutations within P of vesicular stomatitis virus that selectively affect viral RNA replication or viral mRNA transcription have been identified, suggesting that the protein plays an important role in regulating viral RNA replication and viral mRNA transcription (7). However, the roles of phosphorylation of paramyxovirus P proteins in viral RNA synthesis have been less defined.…”
mentioning
confidence: 99%
“…The last 11 amino acids of this domain are highly conserved and contain a number of basic residues that are important for P protein function in mediating the binding of P protein to N-RNA template (15).…”
mentioning
confidence: 99%